Disfuncionalidad familiar y el estado emocional en los estudiantes de bachillerato de la Unidad Educativa del Milenio Carlos Alberto Aguirre Avilés, en la Parroquia La Unión, Provincia de Los Ríos. - Mendez Rizzo, Gladys Stephany (2025)
The present investigation aims to determine the influence of family dysfunctionality on the emotional state of high school students of the Carlos Alberto Aguirre Avilés Millennium Educational Unit, in the parish of La Unión, province of Los Ríos. Family dysfunctionality is characterized by inadequate interaction patterns, such as lack of communication, frequent conflicts and confusing roles, which affect the emotional development of adolescents. The emotional state of students is related to factors such as anxiety, stress and sadness, which influences their academic performance and general well-being. A non-experimental research design was used, with a quantitative approach and correlational scope. The sample consisted of 151 students selected through a proportional stratified probability sampling. Validated instruments were used to collect data, such as the Family Cohesion and Adaptability Scale (FACES III) and the Beck Anxiety Inventory (BAI). The results showed a significant correlation between family dysfunction and the emotional state of students, highlighting the need to intervene in family dynamics to promote their overall well-being, since they show notable behaviors such as problems at home, lack of dialogue, problematic behaviors, among others. Therefore, these circumstances affect the development of emotions in adolescents. In addition, the poor academic performance that occurs in schoolchildren is a result of the various situations that occur at home.